The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.15761/tec.1000125
|View full text |Cite
|
Sign up to set email alerts
|

The role of health insurance in pediatric ambulance use: are children just small adults?

Abstract: Objective: Rapidly rising healthcare costs require a thorough analysis of all the components of care. Multiple studies of adult patients with public insurance or without private insurance have shown that they are more likely than those with private insurance to use the ambulance. Multiple studies of pediatric ambulance use have been limited in generalizability because they rely on individual hospital or single statewide databases and do not specifically look at insurance. The purpose of this study was to descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Several studies have found a significant link between location and non-emergency calls to the ambulance for children; in particular, urban areas were associated with more ambulance use 3 20. One study assessing the ‘appropriateness’ of ambulance use in paediatrics presenting to the emergency department (ED) identified a higher rate of what the authors termed as ‘misuse’ of ambulances for children in urban populations, and suggested that suburban parents would be less likely to call the ambulance ‘inappropriately’.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have found a significant link between location and non-emergency calls to the ambulance for children; in particular, urban areas were associated with more ambulance use 3 20. One study assessing the ‘appropriateness’ of ambulance use in paediatrics presenting to the emergency department (ED) identified a higher rate of what the authors termed as ‘misuse’ of ambulances for children in urban populations, and suggested that suburban parents would be less likely to call the ambulance ‘inappropriately’.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported that Medicaid patients account for the majority of non-emergency calls to the ambulance for children; 43% of patients were insured by Medicaid, (the US federal and state programme that helps with medical costs for people with limited income) and 60% of what the authors termed as ‘unnecessary’ calls were to those without commercial insurance 21. Further studies also concluded that non-insured paediatric patients had significantly higher rates of ambulance use compared with those who were privately insured 20 23 25…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations